The Determinant Effect of Internal Audit Quality With Fraud Prevention Coordination as Mediation - Handayani, Handayani; Suratno, Suratno; Murni, Yetty; Harnovinsah, Harnovinsah; Djaddang, Syahril (Jurnal Pendidikan Akuntansi & Keuangan, 2024)
This research aims to test and analyze the influence of auditor experience, auditor independence and budget time pressure on internal audit quality and fraud prevention coordination. Apart from that, it also tests and analyzes the mediation of fraud prevention coordination on the influence of auditor experience, auditor independence and budget time pressure on the quality of internal audits in local government internal supervisory apparatus in the Bali region. The findings in this research prove that internal audit quality and fraud prevention coordination are significantly influenced by auditor experience and auditor independence, internal audit quality and fraud prevention coordination are not significantly influenced by budget time pressure, fraud prevention coordination is able to partially mediate the influence of auditor experience on audit quality. internal but unable to mediate the influence of auditor independence and budget time pressure on internal audit quality.